Real-time collision detection. - Ericson, Christer, ....- (Amsterdam : Elsevier, 2005)
Written by an expert in the game industry, Christer Ericson's new book is a comprehensive guide to the components of efficient real-time collision detection systems. The book provides the tools and know-how needed to implement industrial-strength collision detection for the highly detailed dynamic environments of applications such as 3D games, virtual reality applications, and physical simulators. Of the many topics covered, a key focus is on spatial and object partitioning through a wide variety of grids, trees, and sorting methods. The author also presents a large collection of intersection and distance tests for both simple and complex geometric shapes. Sections on vector and matrix algebra provide the background for advanced topics such as Voronoi regions, Minkowski sums, and linear and quadratic programming. Of utmost importance to programmers but rarely discussed in this much detail in other books are the chapters covering numerical and geometric robustness, both essential topics
for collision detection systems. Also unique are the chapters discussing how graphics hardware can assist in collision detection computations and on advanced optimization for modern computer architectures. All in all, this comprehensive book will become the industry standard for years to come. *Presents algorithms and data structures with wide applications to the fields of game development, virtual reality, physically based simulation, CAD/CAM, architectural and scientific visualization, molecular modeling, engineering simulation, GIS, ray tracing, and more. *Describes tested, real-world methods, liberally illustrated by C & C++ code. *Reviews necessary concepts from mathematics and computational geometry, and includes extensive references to other sources and research literature. Table of Contents Ch. 1 Introduction Ch. 2 Collision detection design issues Ch. 3 A math and geometry primer Ch. 4 Bounding volumes Ch. 5 Basic primitive tests Ch. 6 Bounding volume hierarchies Ch. 7 Spatial
partitioning Ch. 8 BSP tree hierarchies Ch. 9 Convexity-based methods Ch. 10 GPU-assisted collision detection Ch. 11 Numerical robustness Ch. 12 Geometrical robustness Ch. 13 Optimization